1994
DOI: 10.2172/10122073
|View full text |Cite
|
Sign up to set email alerts
|

Flammable gas safety program. Analytical methods development: FY 1993 progress report

Abstract: • Six samples of core segments from Tank 101-SY, obtained during the window E core sampling, have been analyzed for organic constituents. Four of the samples were from the upper region, or convective layer, of the tank and two were from the lower, nonconvective layer. The samples were analyzed for chelators, chelator fragments, and several carboxylic acids by derivatization gas chromatography/mass spectrometry (GC/MS). The major components detected were ethylenediaminetetraacetie acid (EDTA), nitroso-iminodiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…tanks SY-101 and SY-103 were shipped from Hanford to LANL for Tc removal experiments with ReillexT"-HPQ. These wastes contain relatively high concentrations of organic complexants (Campbell et al, 1993). Ion exchange column experiments on CC simulants and batch contact experiments on the actual CC waste samples were performed at LANL to determine the equilibrium and kinetic parameters for Tc removal using the ReillexTM-HPQ material.…”
Section: Needmentioning
confidence: 99%
“…tanks SY-101 and SY-103 were shipped from Hanford to LANL for Tc removal experiments with ReillexT"-HPQ. These wastes contain relatively high concentrations of organic complexants (Campbell et al, 1993). Ion exchange column experiments on CC simulants and batch contact experiments on the actual CC waste samples were performed at LANL to determine the equilibrium and kinetic parameters for Tc removal using the ReillexTM-HPQ material.…”
Section: Needmentioning
confidence: 99%
“…In To address this need we adapted existing methods for cesium ion removal currently performed on flammable gas tank waste (Campbell et al 1994) to the ferrocyanide tank waste. This method has been successfully demonstrated for the removal of significant levels of radioactivity from tank samples to allow bench-top handling.…”
Section: Influence Ofph On Nitrite Reactivity With Fe(cn)z-mentioning
confidence: 99%
“…The positive ion spectrum of NTA is shown in Figure 3. 22. The (M+Na)+ ion is at m/z 215 and the di-Na ion at m/z 237.…”
Section: Under Rapid Heating Conditions Organic Compounds Favor Vapomentioning
confidence: 99%
“…The identity of the most concentrated component was verified with high resolution MS measurements. B.19 The chelators and chelator fragments constitute only 20-50% of the TOC; it has been shown that the remaining components are low-molecular-weight acids such as oxalic, glycolic, and formic acid (22). Certain of these chelator components in the radioactive environment of the waste tanks degrade rapidly.…”
Section: Deuterated Edta As a Surrogate Tracermentioning
confidence: 99%